URGENCY CERTIFICATION HALAL FOR MSMEs FOOD AND DRINK AMONG THE MUSLIM COMMUNITY OF BANGKA BELITUNG: BETWEEN NEEDS AND FORMALITY - Ahmad Fauzi; Achmad (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to explore halal certification for businesses. Micro, Small, And Intermediate (MSMEs) in sector food and beverages in Bangka Belitung. Using survey methods and quantitative data analysis, this study identified the level of awareness and understanding of halal certification among MSMEs and analyzed its influence on Muslim consumers' purchasing decisions. The results showed that only 45% of MSMEs understood halal certification requirements, while 67% considered the cost and complexity of the process as major barriers. On the other hand, 78% of Muslim consumers stated that halal certification was a major factor in choosing a product, with 62% willing to pay more for halal-certified products. The study also found that halal certification can increase MSME sales by up to 30% after receiving certification. Furthermore, the government's role in providing education and technical support is crucial to increasing MSME participation in the certification process. These findings expected can give outlook for stakeholders policies and business actors in optimizing the potential of the halal market in Indonesia.